Towards a Model of Urban Evolution—Part I: Context - Daniel Silver; Patrick Adler; Mark S. Fox (Urban Science, 2022)
This paper seeks to develop the core concepts of a model of urban evolution. It proceeds in four major sections. First, we review prior adumbrations of an evolutionary model in urban theory, noting their potential and their limitations. Second, we turn to the general sociocultural evolution literature to draw inspiration for a fresh and more complete application of evolutionary theory to the study of urban life. Third, building upon this background, we outline the main elements of our proposed model, with special attention to elaborating the value of its key conceptual innovation, the “formeme”. Last, we conclude with a discussion of what types of research commitments the overall approach does or does not imply, and point toward the more formal elaboration of the model that we undertake in “Towards a Model of Urban Evolution, Part II” and “Towards a Model of Urban Evolution, Part III”. In “Towards a Model of Urban Evolution, Part IV” we demonstrate the application of the model to Yelp data.